Sphingosine-1-phosphate-activated TRPC1 channel controls chemotaxis of glioblastoma cells. Issue 6 (December 2016) - Lepannetier, Sophie; Zanou, Nadège; Yerna, Xavier; Emeriau, Noémie; Dufour, Inès; Masquelier, Julien; Muccioli, Giulio; Tajeddine, Nicolas; Gailly, Philippe
Graphical abstract: Highlights: PDGF triggers the targeting of TRPC1 channel to the front edge of lamellipodia of glioblastoma cells. PDGF activates TRPC1 via sphingosine-1-phosphate signaling pathway. S1P-activated TRPC1 channels control cell chemotaxis. Abstract: TRP channels are involved in the control of a broad range of cellular functions such as cell proliferation and motility. We investigated the gating mechanism of TRPC1 channel and its role in U251 glioblastoma cells migration in response to chemotaxis by platelet-derived growth factor (PDGF). PDGF induced an influx of Ca 2+ that was partially inhibited after pretreatment of the cells with SKI-II, a specific inhibitor of sphingosine kinase producing sphingosine-1-P (S1P). S1P by itself also induced an entry of Ca 2+ . Interestingly, PDGF- and S1P-induced entries of Ca 2+ were lost in siRNA-TRPC1 treated cells. PDGF-induced chemotaxis of U251 cells was dramatically inhibited in cells treated with SKI-II. This effect was almost completely rescued by addition of synthetic S1P. Chemotaxis was also completely lost in siRNA-TRPC1 treated cells and interestingly, the rescue of migration of cells treated with SKI-II by S1P was dependent on the expression of TRPC1. Immunocytochemistry revealed that, in response to PDGF, TRPC1 translocated from inside of the cell to the front of migration (lamellipodes). This effect seemed PI3K dependent as it was inhibited by cell pre-treatment with LY294002, a PI3-kinase inhibitor. Our results thus identify S1P as a potential activator of TRPC1, a channel involved in cell orientation during chemotaxis by PDGF.